Selfie at a museum: Defining a paradigm for an analysis of taking (self-portrait) photographs at museum exhibitions - Chlebus-Grudzień, Patrycja (Turyzm/Tourism, 2018)
Due to the development of social media, posting one's photos is becoming increasingly popular; they often take the form of, so called, ‘selfie’. The phenomenon of photographing oneself has also occurred in cultural institutions, including museums. The museums are implementing various strategies of reacting to people taking pictures of themselves with exhibits at the background. The article presents an analysis of these reactions, and, based on that, various ways of defining the functions and role of the contemporary museum. The author also attempts to provide an answer to the following question: is posting photographs by visitors an element of creating their own image (‘the Culture of Narcissism’), or is it rather a form of interaction with heritage, of a dialogue with the presented contents (‘remix culture’)?